The Potency of the Tumih Village Farmer Community's Participation in the Agricultural Development Planning Strategy - Surti Surti; Syahrial Shaddiq; Ahmad Suhaimi; Muhammad Helmy Abdillah (Gorontalo Development Review, 2022)
In Tumih Village, Wanaraya District, Barito Kuala Regency, South Kalimantan Province, this study attempts to assess the strategy and growth of the agricultural sector as well as the level of community engagement in relation to agriculture. The settlement of Tumih itself has excellent potential for agriculture, particularly rice production. The analytical technique used employs the Strength Field Analysis approach to identify development plans and Participation Strength Analysis to identify the level of community involvement in agriculture in Tumih Village while determining the agricultural sector's strategy. The analysis' findings indicate that the key influencing elements for agricultural development plans in Tumih Village are the availability of human resources in the agricultural sector, particularly in the case of rice, and the farmers' receptivity to new technology. A hindrance in Tumih Village is the absence of irrigation and agricultural technologies. With only 36.5 percent, the assessment of the level of community involvement in planning for agricultural growth is still insufficient.